2012
DOI: 10.1007/s12013-012-9468-5
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol Interferes with Both Type I and Type II Topoisomerase Activities Without Generating Strand Breaks

Abstract: A considerable number of agents with chemotherapeutic potentials reported over the past years were shown to interfere with the reactions of DNA topoisomerases, the essential enzymes that regulate conformational changes in DNA topology. Gossypol, a naturally occurring bioactive phytochemical is a chemopreventive agent against various types of cancer cell growth with a reported activity on mammalian topoisomerase II. The compounds targeting topoisomerases vary in their mode of action; class I compounds act by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Given that vast majority of compounds, covering a number of ellipticine derivatives effective on tumor cells were reported to exert their effects through interfering with topoisomerase II reactions we screened the activities of the derivatives against DNA topoisomerase II reactions (Senarisoy et al 2013;Ashley and Osheroff 2014;Miller et al 2012;McClendon and Osheroff 2007). We therefore employed decatenatiation, intercalation, and cleavage assays.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that vast majority of compounds, covering a number of ellipticine derivatives effective on tumor cells were reported to exert their effects through interfering with topoisomerase II reactions we screened the activities of the derivatives against DNA topoisomerase II reactions (Senarisoy et al 2013;Ashley and Osheroff 2014;Miller et al 2012;McClendon and Osheroff 2007). We therefore employed decatenatiation, intercalation, and cleavage assays.…”
Section: Resultsmentioning
confidence: 99%
“…Decatenation assay is specific for topoisomerase II activity. It is based on the detection of kinetoplast DNA, the mitochondrial DNA of Crithidia fasciculata found as a catenated network of DNA rings (Senarisoy et al 2013). All of the derivatives, Z-1, Z-2, Z-5, and Z-6, inhibited decatenation activity of topoisomerase II at 0.2 mM concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gossypol (GSP), 5 (Chart 1) is a natural polyphenol isolated from cotton plant, Gossypium (Malvaceae). In 2013, Senarisoy M. et al, (Senarisoy et al, 2013) reported that 5 is able to inhibit both TopoI and TopoII enzymes, and in particular this compound belongs to the class of the catalytic inhibitors.…”
Section: Gossypol From Gossypiummentioning
confidence: 99%